The Asymmetric Effects of Monetary Policy in General Equilibrium - Castillo, Paul (2008)
The study involved extending a dynamic general equilibrium neoKeynesian model by considering preferences that exhibit intertemporal nonhomotheticity. Introducing this feature generates a state-dependent intertemporal elasticity of substitution, which induces asymmetric shifts in aggregate demand in response to monetary policy shocks. The effect, in combination with a convex Phillips curve, generates in equilibrium asymmetric responses in output and inflation to monetary policy shocks similar to those observed in the data. In particular, a higher response of both output and inflation to policy shocks exists when economy growth is temporarily high than temporarily low.